Challenges of Crime in City Slums: A Case Study of Mathare Slum in Nairobi County, Kenya - Mwanza, Martin Mwaka (Advances in Social Sciences Research Journal, 2023)
This study focuses on the challenges of crime within Mathare slum in Nairobi County, Kenya. It has been necessitated by the continued concern on the constant presence of crime within the slum areas of Nairobi. Although there have been studies carried out on various challenges in slums, this study provides a detailed analysis of the security challenges faced by Mathare slum dwellers. The study sought to examine five major thematic areas; major causes of crime in Mathare slum, types and trends of crime within Mathare slum, crime reporting, criminal gangs in Mathare slum and fear of crime within Mathare slum. Questionnaires and key informant interviews were used to obtain data from respondents who included Mathare slum residents, police officers, area chiefs and community policing committees’ chairpersons from the thirteen villages in Mathare slum. The challenges of crime in Mathare slum were found to be a combination of multiple factors working in congruence to influence the commission of crime.